Technology Readiness During the COVID-19 Pandemic: Lessons Learned from Indonesia - Genoveva; Jhanghiz Syahrivar; Eka Srirahayu Ariestiningsih (CommIT (Communication and Information Technology) Journal, 2023)
The COVID-19 pandemic since March 2020 has forced Indonesians to practice physical distancing and carry out their personal and professional activities from home. However, not everyone is ready to conduct their regular activities remotely. The issue is the readiness for digital technology. The research aims to analyze the Indonesian people’s readiness for digital technology during the pandemic. The research also investigates the impact of optimism and technology adoption on behavioral intention mediated by perceived ease of use. The research applies a quantitative study using an online questionnaire. The population of the research is people who use Internet technology for online learning, working from home, online shopping, and social activities during the COVID-19 pandemic. The research successfully gathered 327 respondents using purposive sampling. The research uses Structural Equation Model (SEM) method via SPSS AMOS software to analyze the data and generate findings. There are several findings. First, optimism has a positive relationship with perceived ease of use. Second, technology adoption relates with perceived ease of use positively. Third, perceived ease of use has a positive relationship with behavioral intention. Last, the empirical evidence for the mediation roles of perceived ease of use is inconclusive. The research also offers some managerial implications.